Apparent coefficient diffusion (ADC) and fractional anisotropy (FA) values of the rotator cuff muscles using DTI at 3-Tesla MRI in the healthy population - Yusof, Mohd Fariq Mohd (2018)
Objective: To determine the value of apparent diffusion coefficient (ADC), and fractional anisotropy (FA) of the rotator cuff muscles using a 3-Tesla MRI in healthy subjects and comparing its differences. Materials and Methods: Thirty-eight healthy volunteers were included in this prospective study. Diffusion tensor magnetic resonance imaging (DT MRI) of the rotator cuff muscles were performed. Single-shot spin-echo echo-planar imaging sequences in 32 diffusion directions with a b-value of 400 s/mm2, was selected as most optimal for this study. Subsequently ADC and FA values of the rotator cuff muscles were acquired from the sagittal oblique view of the shoulder by manually drawing an elliptical range of interest of the visualised muscles. Statistical analysis carried out using One-Way ANOVA post-hoc Scheffe test. Measurement was taken by two ratters to reduce bias. Results: Mean ADC with standard deviation of the supraspinatus was 1.63 (±0.12), infraspinatus was 1.61 (±0.09) and subscapularis muscle was 1.74 (±0.15). Mean FA with standard deviation of the supraspinatus was 0.45 (±0.05), infraspinatus was 0.41 (±0.36), subscapularis muscle was 0.47 (±0.55). Mean difference of ADC between supraspinatus and subscapularis muscles as well as subscapularis and infraspinatus muscles were significantly different. The mean ADC between the Supraspinatus and infraspinatus muscles mean difference were similar. Mean difference of FA between all 3 pairs of muscles were significantly different. Intraclass Coefficient for FA and ADC between 2 Raters ranges from good to excellent results. Conclusion: This study has been able to obtain normal range of values of FA and ADC. Among healthy subjects using DTI on a 3-Tesla MRI. These two means are reliable.